Pengaruh Kualitas Pelayanan Receptionist Terhadap Kepuasan Dan Loyalitas Pelanggan Di Royal Safari Garden Resort & Convention - Fatimah, Sithy; Rahmanita, Myrza; ., Nurbaeti (Jurnal Ilmiah Pariwisata, 2017)
This study aims to determine the Influence of Service Quality Recptionist Against Customer Satisfaction And Loyalty At Royal Safari Garden Resort & Convention. This type of research is survey research. With a population of guests who have stayed at the Royal Safari Garden Resort & Convention as many as 4152 people. The sampling technique is purposive sampling. The number of samples in this study amounted to 100 people. Data collection technique is done by using questionnaire (questionnaire) by using Likert scale that has been tested the validity and reliability. The results concluded that; (2) There is direct and significant influence between customer satisfaction to customer loyalty with strength 0,614, (3) There is direct and significant influence between service quality to loyalty Customer with influence strength 0,841, (4) There is indirect influence between service quality to customer loyalty with customer satisfaction as intervening variable equal to 0,668, (5) The biggest influence of service quality dimension to satisfaction is reliability (reliability) equal to 0,822 and responsiveness (power Responsiveness) of 0.797, the smallest influence sedangka is empathy (empathy) of 0.099